Comparison of six-minute walking tests conducted with and without supplemental oxygen in patients with chronic obstructive pulmonary disease and exercise-induced oxygen desaturation - Ozalevli, Sevgi (Ann Saudi Med, 2007)
BACKGROUND: There are contradictory reports in the literature on the effects of supplemental oxygen administered before or after exercise tests. In light of this, we compared the results of 6-minute walking tests performed in room-air conditions (A6MWT) and with supplemental oxygen (O6MWT) in patients with chronic obstructive pulmonary disease (COPD) and exercise-induced oxygen desaturation. PATIENTS AND METHODS: Thirty-one patients with COPD were included in the study. The A6MWT and O6MWT were performed in randomized order on each patient. During the tests, severity of dyspnea and tiring of the leg were evaluated by the Modified Borg Scale. Heart rate and pulsed oxygen saturation and blood pressure were measured by pulse oximeter. RESULTS: Walking distance was longer with the O6MWT than with the A6MWT (P=0.001). The O6MWT resulted in a smaller increase in dyspnea, leg fatigue, and heart rate and a smaller drop in pulsed saturation than the A6MWT (P<0.05). The walking distance with the O6MWT correlated with respiratory function and hemodynamic parameters (P<0.05). CONCLUSION: The O6MWT, which produced less hemodynamic stress and was safer than the A6MWT, might provide more accurate information on exercise limitation for patients with COPD. These results suggest that the O6MWT can be used as a standard walking exercise test for patients with COPD and exercise-induced oxygen desaturation.